2020
DOI: 10.1007/s12161-020-01885-2
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometric Classification of Bamboo Shoot Species by Comparison of Different Machine Learning Methods

Abstract: The nutrition and quality of bamboo shoots from different species have a large variation, and traditional methods used for the classification of different bamboo shoot species are expensive and time-consuming. Here, the capability of near-infrared reflectance (NIR) spectroscopy to identify bamboo shoot species in a time-and cost-effective manner was examined. The NIR spectra of four bamboo shoot species were collected. Three classification models, a support vector machine (SVM), partial least squaresdiscrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Since then, through over half a century of development, it has matured and is now widely employed in food, medicine, petrochemical, and other research fields (Mohamed et al, 2018 ; Guo et al, 2020 ). In recent years, NIR spectroscopy technology has become increasingly and broadly used in forestry, for example, to estimate photosynthetic characteristics (Dechant et al, 2017 ), to predict leaf-level nitrogen content (Kokaly, 2001 ), to distinguish bamboo shoots of different qualities (Tong et al, 2020 ), and to name a few applications. Partial least squares (PLS) regression, a quick, efficient, and optimal regression method based on covariance, is a widely used chemometric method, one that combines the advantages of multiple linear regression, canonical correlation analysis, and principal component regression (Tenenhaus et al, 2005 ; Sarker and Nichol, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, through over half a century of development, it has matured and is now widely employed in food, medicine, petrochemical, and other research fields (Mohamed et al, 2018 ; Guo et al, 2020 ). In recent years, NIR spectroscopy technology has become increasingly and broadly used in forestry, for example, to estimate photosynthetic characteristics (Dechant et al, 2017 ), to predict leaf-level nitrogen content (Kokaly, 2001 ), to distinguish bamboo shoots of different qualities (Tong et al, 2020 ), and to name a few applications. Partial least squares (PLS) regression, a quick, efficient, and optimal regression method based on covariance, is a widely used chemometric method, one that combines the advantages of multiple linear regression, canonical correlation analysis, and principal component regression (Tenenhaus et al, 2005 ; Sarker and Nichol, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another work, Aggarwal et al [37] presented an image and morphological-based optimized random forest classification method to recognize Indian oxygen plants using SVM, RF, and multilayer perceptron (MLP) classifiers. Tong et al [53] also performed bamboo shoot species classification using the capability of near-infrared reflectance (NIR) spectroscopy and three ML algorithms, which was less expensive and more time-efficient. Three classification models, i.e., SVM, RF, and partial least squares discriminant analysis (PLS-DA), were used.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Three classification models, i.e., SVM, RF, and partial least squares discriminant analysis (PLS-DA), were used. The SVM classifier demonstrated the most significant classification accuracy, reaching 95% in some cases [53].…”
Section: Background and Related Workmentioning
confidence: 99%
“…It was found that the SVM model with second derivative treatment performed the best. The combination of NIR spectra and the SVM method provides a fast and non-destructive method for the classification of bamboo shoot species [28]. A portable NIR sensor was used to predict the freshness of eggs.…”
Section: Support Vector Machine (Svm) Modelmentioning
confidence: 99%